Study on the Influence of Parameter Fluctuation on Ethylene Epoxidation Reaction Process - Feng Wang (IEEE Access, 2019)
Ethylene epoxidation reactor is a kind of critical equipment in an oxidation unit. Due to the complex coupling effect of the extreme operating environment of high temperature, high pressure and potential risk factors, the reactor tends to work abnormally under the impact of parameter fluctuation, and temperature runaway incident may occur and cause severe loss. For studying the influence of parameter fluctuation on ethylene epoxidation reaction process and preventing temperature runaway accidents, physical modeling is performed firstly in this paper to acquire the chemical reaction mechanism therein and confirm the operation parameters which should be focused. The unsteady simulation of the operation process under normal situation has been performed. On such basis, a test of single-factor effect is performed to analyze the impact of parameter fluctuation on the temperature balance and operation efficiency of the reactor. Comparison analysis has been carried out between the simulation data acquired according to the established model and real production data, and it was found that the result is consistent. The analysis result indicates: higher ethene concentration, oxygen concentration, feed flux, feed temperature, drum temperature, operating pressure or smaller porosity may improve bed temperature and accelerate reaction rate; therein, ethene concentration, oxygen concentration, drum temperature, and porosity are operation parameters that need special monitoring. Based on the risk analysis of the ethylene epoxidation reactor and the simulation of the impact of parameter fluctuation, this paper studies the cause of the reactor's temperature runaway to provide a technical basis for the forecast of reactor's temperature runaway, early warning, and high-efficient operation of equipment. Model established based on abnormal condition parameters fluctuation, can contribute to early warning reactor temperature runaway, revealing the influence mechanism of parameter fluctuation for the reaction system, monitoring reaction process, eliminating temperature runaway in the bud, and providing theoretical and technical basis for petrochemical equipment fault diagnosis, accident prevention and control and safely long-time running.